Understanding Suicidality in Pacific Adolescents in New Zealand Using Network Analysis - Gossage, Lisa; Narayanan, Ajit; Dipnall, Joanna; Berk, Michael; Sumich, Alexander; Haslbeck, Jonas; Iusitini, Leon; Wrapson, Wendy; Tautolo, El-Shadan; Siegert, Richard (Wiley, 2023)
Introduction: Pacific adolescents in New Zealand (NZ) are three to four times more likely than NZ European adolescents to report suicide attempts and have higher rates of suicidal plans. Suicidal thoughts, plans, and attempts, termed suicidality in this study, result from a complex dynamic interplay of factors, which emerging methodologies like network analysis aim to capture. Methods: This study used cross-sectional network analysis to model the relationships between suicidality, self-harm, and individual depression symptoms, whilst conditioning on a multi-dimensional set of variables relevant to suicidality. A series of network models were fitted to data from a community sample of New Zealand-born Pacific adolescents (n = 550; 51% male; Mean age (SD) = 17 (0.35)). Results: Self-harm and the depression symptom measuring pessimism had the strongest associations with suicidality, followed by symptoms related to having a negative self-image about looks and sadness. Nonsymptom risk factors for self-harm and suicidality differed markedly. Conclusions: Depression symptoms varied widely in terms of their contribution to suicidality, highlighting the valuable information gained from analysing depression at the symptom-item level. Reducing the sources of pessimism and building self-esteem presented as potential targets for alleviating suicidality amongst Pacific adolescents in New Zealand. Suicide prevention strategies need to include risk factors for self-harm.
Keywords: adolescents; network analysis; pessimism; psychopathology; self-harm; suicidality; 52 Psychology; Behavioral and Social Science; Pediatric; Mental Health; Serious Mental Illness; Suicide; Suicide Prevention; Clinical Research; Depression; Prevention; 2 Aetiology; 2.3 Psychological, social and economic factors; Mental health; 3 Good Health and Well Being; 1701 Psychology; Psychiatry; 4203 Health services and systems; 5203 Clinical and health psychology; Humans; Male; Adolescent; Female; Suicidal Ideation; Cross-Sectional Studies; New Zealand; Suicide; Suicide, Attempted; Risk Factors